Effects of Aquatic Exercise and Floor Curling on Balance Ability and Lower Limb Muscle Strength in Children with Intellectual Disabilities: A Pilot Study in China - Peiting Zhao; Gaohui Zhu; Sha Chen; Yu Pan; Kai Chen; Li Huang; Liya Guo (MDPI AG, 2024)
Children with intellectual disabilities often face challenges in balance ability and lower limb muscle strength, which negatively impact their daily lives and motor function. Therefore, it is crucial to enhance the balance ability and lower limb muscle strength of children with intellectual disabilities. This study aimed to investigate the effects of a 12-week aquatic exercise and floor curling intervention on the balance ability and lower limb muscle strength of children with intellectual disabilities. Forty-two participants were randomly assigned to the aquatic exercise group, floor curling group, and control group. The aquatic exercise and floor curling groups received a 12-week intervention, while the control group engaged in supervised free activities. The participants' balance ability and lower limb muscle strength were assessed using the Berg Balance Scale and a muscle strength testing device before and after the intervention. The results showed significant improvements in balance ability and lower limb muscle strength for both the aquatic exercise group and the floor curling group after the intervention. The aquatic exercise group demonstrated an average improvement of 10.84% in balance ability and an overall average improvement of 16.28% in lower limb muscle strength. The floor curling group showed an average improvement of 9.04% in balance ability and an overall average improvement of 15.67% in lower limb muscle strength. These improvement results were statistically significant (p < 0.05) and ranged from medium to large effect sizes (d = 0.5~0.8). The findings of this study validate the positive effects of aquatic exercise and floor curling on the balance ability and lower limb muscle strength of children with intellectual disabilities. These interventions can be considered effective approaches for functional rehabilitation in children with intellectual disabilities.